Pesticide residues in brain tissues of dairy cattle in Lembang - Indraningsih Indraningsih; Yulvian Sani (Jurnal Ilmu Ternak dan Veteriner, 2006)
The use of pesticides to control plant diseases may cause residual formation in crops, its byproduct and environmental. Furthermore, the use of agriculture byproduct as animal feed may cause poisoning or residual formation in animal products. The purpose of this study is to investigate of pesticide residues in brain tissues of dairy cattle in relation to animal feed as a contamination source. Samples consisted of animal feeds (19 samples of fodder and 6 samples of feed), 31 samples of sera and 25 samples of brain tissues of dairy cattle collected from Lembang, West Java. Feeds and fodders were collected from dairy farms located in Lembang. Sera were directly collected from 31 heads of Frisien Holstein (FH) cattle from the same location, while brain tissues of FH cattle were collected from a local animal slaughtering house. Pesticide residues were analysed using gas chromatography (GC). Both residues of organochlorines and organophosphates were detected from brain tissues with average residue concentration OP was 22.7 ppb and OC was 5.1 ppb and a total residue was 27.8 ppb. The pesticide residues in brain tissues are new information that should be taken into consideration since the Indonesian consumed this tissues as an oval. Although pesticides residue concentration was low, pathological changes were noted microscopically from the brain tissues including extracellular vacuolisation, focal necrosis, haemorrhages, dilatation of basement membrane without cellular infiltration. Both pesticide residues were also detected in sera, where OP (9.0 ppb) was higher than OC (4.9 ppb). These pesticides were also detected in animal feeds consisting fodders and feeds. Residues of OP (12.0 ppb) were higher than OC (1.8 ppb) in feeds, but residues of OP (16.8 ppb) were lower than OC (18.7 ppb) in fodders. Although, pesticide residues in sera and brain tissues were below the maximum residue limits (MRL) of fat, the presence of pesticides in brain tissues should be taken into consideration as their effects in brain lesions. There was a correlation between contaminant found in animal feeds and pesticide residues in sera and brain tissues of dairy cattle.Key Words: Pesticides, Residues, Brain, Dairy Cattle